A NICE fallacy. Issue 8 (30th July 2007) - Quigley, Muireann
Abstract : A response is given to the claim by Claxton and Culyer, who stated that the policies of the National Institute for Health and Clinical Excellence (NICE) do not evaluate patients rather than treatments. The argument is made that the use of values such as quality of life and life-years is ethically dubious when used to choose which patients ought to receive treatments in the National Health Service (NHS).